The Influence of Village Tourism Development Strategy and Community Economic Growth on the Success of the Telaga Agrotourism Management Group in Madiredo Village, Pujon, Malang Regency - Anggraini, Putri; Zulkarnain, Zulkarnain; Choiro, Umu Da’watul (Universitas Negeri Malang, 2024)
The development of a tourism village is one of the efforts that can be pursued to enhance the welfare of village development and the local community, provided that the strategies used align with the sustainable quality of natural and human resources. The success of the management group is crucial in transforming the tourism site from being enjoyed solely by the local community to becoming a tourist destination. This study aims to determine the influence of tourism village development strategies and community economic growth, both partially and simultaneously, on the success of the agrotourism management group. This research is quantitative. The population in this study consists of the residents of Lebo Hamlet, with a sample selected using non-probability sampling, specifically purposive sampling, and applying the Slovin formula. Data collection was conducted by distributing questionnaires to 86 respondents. The data analysis techniques used in this study include validity and reliability tests, classical assumption tests, and hypothesis tests. The results indicate that, partially, the tourism development strategy variable has a t-value greater than the t-table value (4.991 > 1.998), with a significance level of 0.000 < 0.05, meaning that the tourism development strategy has a positive and significant effect on the success of the management group. The highest level in the frequency analysis is the cooperation indicator. Partially, the community economic growth variable has a t-value greater than the t-table value (2.151 > 1.998), with a significance level of 0.034 < 0.05, indicating that community economic growth has a positive and significant effect on the success of the management group. Simultaneously, the variables of tourism development strategy and community economic growth show a significance value of 0.000 < 0.05, indicating that both variables significantly affect the success of the management group. Keywords: Development Strategy, Economic Growth, Group Success, Tourism Village